Handbook of Economic Nationalism - Pickel, Andreas (Edward Elgar Publishing Limited, 2022)
This cutting-edge Handbook puts economic nationalism in its historical context, from early industrialization to globalization. It explores how economic nationalism has emerged to new prominence in the post-globalization era as states are trying to protect their economies, societies, and cultures from unwanted external influences.